Release of dangerous substances from CDW used in road pavements. Laboratory and field leaching tests - Martins, I. M. (2015)
The use of Construction and Demolition Recycled Materials in sub-base layers of road pavements is analysed from an environmental perspective based on the results of leaching tests.